Contingency contracts for weight gain of patients with anorexia nervosa in inpatient therapy: practice styles of specialized centers - Ziser, Katrin; Nikendei, Christoph (Journal of Clinical Medicine, 2018)
The treatment of patients with anorexia nervosa (AN) is often challenging, due to a high degree of ambivalence towards recovery and weight gain these patients often express. One part of the multimodal treatment is the utilization of treatment contracts (i.e., contingency contracts) that aim to motivate patients to gain weight by applying positive and negative consequences for the (non-)achievement of weight goals. The main aim of this study is to assess and analyze current standards of contingency contracts’ utilization in German eating disorder centers. n = 76 mental health professionals of twelve specialized university centers in Germany that are currently or were formerly treating patients with AN in an inpatient setting participated. Most experts use contingency contracts in their clinic with weekly weight goals ranging between 500 and 700 g. Overall effectiveness and significance of contingency contracts for the inpatient treatment of patients with AN was rated high. Typical characteristics of a contingency contract in specialized German university hospital centers, such as the most frequent consequences, are described. The survey results assist the planning of further studies aiming to improve the multimodal treatment of patients with AN. For clinical practice, using external motivators such as contingency contracts as well as targeting internal motivation (e.g., by using motivational interviewing) is proposed.
Gesehen am 03.04.2020